Enhancing TARIG Transform-Based Encryption Using Nonlinear Permutation Polynomial over Prime Fields - Domven, Lohcwat; Danladi, Daniel; Peter, Patrick Pam; Bailey, Abbas Saleh (Mikailalsys Journal of Advanced Engineering International, 2025)
The Affine Cipher, when implemented via the Tarig Transform, provides a straightforward and efficient approach to data encryption but is constrained by a limited key space and susceptibility to known-plaintext attacks. To overcome these shortcomings, this study proposes an enhanced encryption scheme that incorporates polynomial-based transformations into the Affine-based Tarig Transform framework. By introducing nonlinear polynomial mappings, the proposed method significantly expands the key space, enhances diffusion properties, and strengthens resistance to cryptanalytic techniques. Experimental evaluations confirm that the polynomial-based approach offers improved security metrics, including greater statistical randomness, while preserving computational efficiency comparable to the original implementation. These findings indicate that the enhanced scheme presents a viable and more secure alternative to conventional Affine Cipher methods for robust data communication.